2005
DOI: 10.1074/jbc.m502974200
|View full text |Cite
|
Sign up to set email alerts
|

Pitx2a Binds to Human Papillomavirus Type 18 E6 Protein and Inhibits E6-mediated P53 Degradation in HeLa Cells

Abstract: Binding of high risk human papillomavirus (HPV) E6 protein to E6-associated protein (E6AP), a cellular ubiquitin-protein ligase, enables E6AP to ubiquitinate p53, leading to p53 degradation in cervical cancer cells such as HeLa cells. Here we report that Pitx2a, a bicoid-type homeodomain transcription factor, can bind to HPV E6 protein and inhibit E6/E6AP-mediated p53 degradation. Deletion of the Pitx2a homeodomain abrogates its ability to bind to HPV E6 protein and to induce p53 accumulation in HeLa cells, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…The effect of exogenously added recombinant p53 on the complex formation was easily assessed in this assay because HeLa cells, which are HPV-E6 transformed, have low levels of p53 expression (Wei, 2005). As shown in Figure 1c, increasing amounts of His-p53 increased both the amount of CstF1 'pulled down' by GST-BARD1 (upper panel, lanes 1-8) and the amount of BARD1 'pulled down' by GST-CstF1 (lower panel, lanes 1-8), indicating that p53 stabilized the CstF1/BARD1 complex.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of exogenously added recombinant p53 on the complex formation was easily assessed in this assay because HeLa cells, which are HPV-E6 transformed, have low levels of p53 expression (Wei, 2005). As shown in Figure 1c, increasing amounts of His-p53 increased both the amount of CstF1 'pulled down' by GST-BARD1 (upper panel, lanes 1-8) and the amount of BARD1 'pulled down' by GST-CstF1 (lower panel, lanes 1-8), indicating that p53 stabilized the CstF1/BARD1 complex.…”
Section: Resultsmentioning
confidence: 99%
“…27 In this regard, it is interesting that Pitx2 has been shown to bind to HPV type 18 E6 protein and inhibit p53 degradation in vitro, leading to the accumulation of functional p53 protein and the induction of cell-cycle arrest in HeLa cells. 30 Whether Pitx2 also transcriptionally activates p53 remains to be determined, but the two family members at least share functional equivalence in terms of p53 function. Here, we have demonstrated that hPitx1 binds directly to the p53 promoter in vitro and in vivo resulting in the transcriptional activation of the p53 gene.…”
Section: Discussionmentioning
confidence: 99%
“…b OSRGA, POS and UMR106: p53 status was defined by immunocytochemistry using a p53 antibody specific for the wild-type (wt) protein. For other cell lines, the p53 status was already defined in the literature (Diller et al, 1990;Casey et al, 1991;Chandar et al, 1992;Florenes et al, 1994;Wei, 2005). c STAT5 activation was studied after 15 min of OSM treatment by western blotting experiment using a P-STAT5 antibody.…”
Section: Proapoptotic Effects Of Osm On Osteosarcoma Cells C Chipoy Ementioning
confidence: 99%
“…The role of p53 in sensitization to apoptosis by OSM was then confirmed by the screening of cell lines with different p53 status (Figure 6d, Table 1 and Supplementary Figure 2 for ROS, ST2 and MG63 cells). Indeed, the combination OSM þ Sts did not induce apoptosis on cell lines which have a defective p53 (mutated or null), like MG63, SaOS2 and MNNG-HOS human osteosarcoma cell lines (Diller et al, 1990;Casey et al, 1991;Chandar et al, 1992;Wei, 2005). The resistant U2OS cells are known to express wild-type p53, but inactivated by an excess of its negative regulatory partner mdm2 (Florenes et al, 1994) and/or loss of its activator p14 ARF (Stott et al, 1998).…”
Section: Stat5 Is Necessary For Apoptosis Induced By Osm þ Stsmentioning
confidence: 99%